Watching the City with Pleasure: Polite Disengagement, Aesthetic Pleasure and Life in the City in The Spectator - Andersen Nexø, Tue (The Nordic Journal of Aesthetics, 2022)
The essay examines the intersection between aesthetic the-ory and representations of the city in the periodical essay The Spectator (1711-1714). Focusing on this intersection allows for an analysis of the cultural work aesthetic pleasure is supposed to do according to The Spectator, and also shows key differenc-es between “spectatorial” and later, Kantian aesthetics. In The Spectator aesthetic pleasure has to do with producing a model for how one should relate to the realm of politics—rather than disin-terest, the precondition of aesthetic pleasure turns out to be disengagement. Read through the lens of the city, aesthetic pleasure turns out to be a key component in The Spectator’s vision of how to live a good life as a privileged subject of a modern state.